Evaluación del proceso de interesterificación enzimática de una mezcla de aceites vegetales para la obtención de una base grasa para margarinas en Sigra S.A (2022)
In the present work, an experimental study was developed in order to evaluate the enzymatic interesterification process of a mixture of vegetable oils to obtain a fat mixture suitable for the production of margarines, based on the physicochemical parameters established by the company SIGRA. SA which are solids curve and melting point.